Regulatory effects of laminin derived peptide on microtissue formation for tissue engineered scaffold-free constructs - Yaralı Çevik, Ziyşan Buse; Ördek, Ayşe; Karaman, Ozan (The European Research Journal, 2022)
Objectives: Vascularization is an important stage for tissues and organs. The vascular network is succeeded by the attachment, spreading, proliferation of endothelial cells, and the completion of endothelialization. Endothelization can be mediated by laminin-derived peptides on microtissues. It is known that laminin-derived Tyr-Ile-Gly-Ser-Arg (YIGSR) peptide contributes to endothelial microtissue formation by promoting increased adhesion and proliferation of endothelial cells. This study aims to determine the efficacy of the laminin-derived YIGSR peptide in Human Umbilicial Vein Endothelial Cell (HUVEC) scaffold free microtissues (SFMs). Methods: After solid phase synthesis of YIGSR, microtissues were formed as SFMs. SFMs were cultured with 0 mM (control group), 1.5 mM and 3 mM YIGSR peptide. Diameters and viability analysis of HUVEC SFMs were performed on the 1st, 4th and 7th days. Results: The diameters of control SFMs group decreased day by day. Diameters of 3 mM YIGSR SFMs increased on the 1st and 4th days but significantly decreased on the 7th day. On the other hand, 1.5 mM YIGSR had a tendency on tissue formation because of increased diameter. As a result of the viability, YIGSR peptide increased cell viability. Conclusions: It has been determined that 1.5 mM YIGSR is the optimum amount for enlargement and viability of HUVEC SFMs. The concentration has contributed to proliferation and viability of endothelial SFMs. Thus, 1.5 mM YIGSR has been found as the most promising peptide concentration for increasing vascularization.